Au nanozyme-based multifunctional hydrogel for inflammation visible monitoring and treatment - Yunjing Jiang; Yuyu Cao; Jie Wu; Rongxian Bai; Shufan Wan; Lei Dai; Jiangtao Su; Hongmei Sun (Materials Today Bio, 2024)
Chronic inflammation can delay wound healing, eventually leading to tissue necrosis and even cancer. Developing real-time intelligent inflammation monitoring and treatment to achieve effective wound management is important to promote wound healing. In this study, a smart multifunctional hydrogel (Hydrogel@Au NCs&DG) was proposed to monitor and treat the wound inflammation. It was prepared by mixing 3-carboxy-phenylboronic acid modified chitosan (CS-cPBA), β-glycerophosphate (β-GP), albumin-protected gold nanoclusters (BSA-Au NCs), and dipotassium glycyrrhizinate (DG) about 10 s. In this hydrogel, CS-cPBA and β-GP are crosslinked together by boric acid ester bond and hydrogen bond to form the main hydrogel network, endowing the hydrogel with self-healing and injectable properties to adapt irregular wounds. Importantly, the as-prepared hydrogel with good biocompatibility and excellent adhesion property could directly determine the H2O2 to monitor the wound microenvironment by visible fluorescence change of BSA-Au NCs and then guide the frequency of dressing change to eliminate inflammation. The results demonstrated that the as-prepared smart hydrogel could be expected to serve as an intelligent wound dressing to promote inflammation-infected wound healing.